KBPM UNIVERSITAS TRIBUANA KALABAHI TAHUN 2025: TRANSFORMASI PRODUK MINYAK KEMIRI UNGGULAN DESA KAMAIFUI - Melki I. Puling Tang (JOURNAL OF COMMUNITY DEDICATION, 2025)
Candlenut is an agricultural product with significant potential for optimal development. This is greatly influenced by the opening of the candlenut market, which is related to the increasing demand for candlenut consumption, both domestically and internationally. The candlenut plant has many uses, such as stimulating hair growth, healing skin wounds, diarrhea, asthma, and enhancing analgesic effects. However, the part of the plant with the highest economic value is the candlenut seed. The implementation method applied to improve the quality of community products in candlenut oil production involves three approaches: processing, packaging design, and packaging, and marketing. The results of the community empowerment fieldwork program conducted by KBPM students in Kamaifui village attempted to participate in supporting the development of candlenut oil products to improve the quality of community products as a source of income in the village.